2010
DOI: 10.1016/j.actamat.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain rate on microstructure of polycrystalline oxygen-free high conductivity copper severely deformed at liquid nitrogen temperature

Abstract: Phenomenological plastic flow stress models are used extensively in the simulation of large deformations of metals at high strain-rates and high temperatures. Several such models exist and it is difficult to determine the applicability of any single model to the particular problem at hand. Ideally, the models are based on the underlying (subgrid) physics and therefore do not need to be recalibrated for every regime of application. In this work we compare the Johnson-Cook, Steinberg-Cochran-Guinan-Lund, Zerilli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 137 publications
1
28
1
Order By: Relevance
“…7, partial dislocation behaviors, formation of SFs and formation of dislocation networks are all enhanced with increasing hydrostatic pressure when the grain size is large (15 nm), which is consistent with results shown in GB thickening is observed to increase monotonically with increasing hydrostatic pressure for both grain sizes, and the NC Cu with grain size of 3 nm has the trend to become amorphous state after 10% strain compression when the hydrostatic pressure is as high as 80 GPa. The crystalline-to-amorphous transition has generally been observed during the high-strain-rate deformation processes [36][37][38]. Meyers et al [36] reported the first observation on crystalline-to-amorphous transition in stainless steel inside a shear band formed under dynamics loading, which was attributed to a non-equilibrium solid-state amorphization process rather than melting.…”
Section: Resultsmentioning
confidence: 99%
“…7, partial dislocation behaviors, formation of SFs and formation of dislocation networks are all enhanced with increasing hydrostatic pressure when the grain size is large (15 nm), which is consistent with results shown in GB thickening is observed to increase monotonically with increasing hydrostatic pressure for both grain sizes, and the NC Cu with grain size of 3 nm has the trend to become amorphous state after 10% strain compression when the hydrostatic pressure is as high as 80 GPa. The crystalline-to-amorphous transition has generally been observed during the high-strain-rate deformation processes [36][37][38]. Meyers et al [36] reported the first observation on crystalline-to-amorphous transition in stainless steel inside a shear band formed under dynamics loading, which was attributed to a non-equilibrium solid-state amorphization process rather than melting.…”
Section: Resultsmentioning
confidence: 99%
“…[33,34] These two features enable twin boundaries to exist (even at high temperature) after deformation and enable the materials to have great strength. [6] High speed and low temperature (over~33 of ln Z) are required for twinning to be activated as one of the main deformation mechanisms in copper, and the twin fraction increases with increasing ln Z. [7,8] Thus, the CTD sample with~64 of ln Z could have many twin boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the effect of the Z parameter at not only extreme but also ordinary conditions, the deformation of copper over a wide range of temperature and strain rate were studied. [6][7][8] However, these studies have three deficiencies: (1) few study at strain rates over~10 3 s À1 and at cryogenic temperature, (2) less consideration for global microstructural features than for local microstructural ones, and (3) insufficient attention to reheating from cryogenic temperature to room temperature after the deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the increase in strain rate causes increase in strain hardening which thereby influences the texture. Zhang et al [10] studied the effect of strain rate on microstructure of polycrystalline oxygen-free high conductivity copper severely deformed at liquid nitrogen temperature. Kodeeswaran et al [11] analysed the effect of strain rate on nanocrystalline surface formation in controlled ball impact process in AISI 304 SS.…”
Section: Introductionmentioning
confidence: 99%